Analisis Vegetasi Pantai Barat Aceh Pasca Tsunami - Djufri Djufri (Universitas Syiah Kuala, 2010)
The objectivees of this research were; to acquered of vegetation in Banda Aceh beach after tsunami, to find expression about of composition, association, species diversity index (H’), similarity index (IS), and species distribution pattern.The stage of research were; observation and segmentation of study area. The size of study area is 420 ha, and sample area is 10% of population. The station of sampling is (a). Meulaboh District Beach (MDB), (b). Aceh Jaya District Beach (AJDB), and Lhoknga District Beach (LDB). For each of sampling location a given ten sampling quadrat with five replication. total sample are 50 quadrats. The observated variable is number of spec ies, absolute diversity, absolute frequency, and absolute dominance. The calculated of importance value used formula is DR + FR + DMR., and calculated of species diversity index with Shannon-Wiener formula. The category of species diversity index is; if H’1 very low category, H’1-2 low category, H’2-3 median category, and H’3-4 high category.The result of this research are; (a). The vegetation physiognomy in Meulaboh District Beach, (b).Aceh Jaya District Beach, and Lhoknga District Beach were fundamental changed after tsunami, (c). The planting of mangrove species in Aceh West Beach didn’t resulted yet optimalization, (d). Dominance of tree in Aceh West Beach were Casuarina equisetifolia, and Cocos nucifera, dominance of underbrush were Calatropis gigantea, and Vernonia cinerea, and dominance of herbs species were Ipomoea pescaprae, and Chloris barbata (5). The moment effort is necessary for serious reclamation in Aceh West Beach after tsunami specific.